Obesity phenotypes and dyslipidemia in adults from four African countries: An H3Africa AWI-Gen study - Engelbert A. Nonterah; Godfred Agongo; Nigel J. Crowther; Shukri F. Mohamed; Lisa K. Micklesfield; Palwendé Romuald Boua; Alisha N. Wade; Solomon S. R. Choma; Hermann Sorgho; Isaac Kissiangani; Gershim Asiki; Patrick Ansah; et al. (PLoS ONE, 2025)
Introduction The contribution of obesity phenotypes to dyslipidaemia in middle-aged adults from four sub-Saharan African (SSA) countries at different stages of the epidemiological transition has not been reported. We characterized lipid levels and investigated their relation with the growing burden of obesity in SSA countries. Methods A cross-sectional study was conducted in Burkina Faso, Ghana, Kenya and South Africa. Participants were middle aged adults, 40–60 years old residing in the study sites for the past 10 years. Age-standardized prevalence and adjusted mean cholesterol, LDL-C, HDL-C, triglycerides and non-HDL-C were estimated using Poisson regression analyses and association of body mass index (BMI), waist circumference (WC) and waist-to-hip ratio (WTHR) with abnormal lipid fractions modeled using a random effects meta-analysis. Obesity phenotypes are defined as BMI ≥ 30 kg/m2, increased WC and increased waist-to-hip ratio. Results A sample of 10,700 participants, with 54.7% being women was studied. Southern and Eastern African sites recorded higher age-standardized prevalence of five lipid fractions then West African sites. Men had higher LDL-C (19% vs 8%) and lower HDL-C (35% vs 24%) while women had higher total cholesterol (15% vs 19%), triglycerides (9% vs 10%) and non-HDL-cholesterol (20% vs 26%). All lipid fractions were significantly associated with three obesity phenotypes. Approximately 72% of participants in the sample needed screening for dyslipidaemia with more men than women requiring screening. Conclusion Obesity in all forms may drive a dyslipidaemia epidemic in SSA with men and transitioned societies at a higher risk. Targeted interventions to control the epidemic should focus on health promoting and improved access to screening services.